Anthropological Witness : Lessons from the Khmer Rouge Tribunal - Hinton, Alexander Laban (Book collections on Project MUSE., 2022)
"This book asks whether scholars who serve as expert witnesses can effectively contribute to tribunals for international atrocity crimes, where the focus is on legal guilt as opposed to academic explanation"--